MODEL RESOLUSI KONFLIK LAHAN DI KESATUAN PEMANGKUAN HUTAN PRODUKSI MODEL BANJAR - Marinus Kristiadi Harun; Haryatno Dwiprabowo (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2014)
Development of Forest Management Unit is considered as solution to improve current forestry institution in Indonesia as it will pave way for implementing principles of forest management on the ground. However, its development is still facing problems, one of them is land tenurial problem. This study aims to analyze land conflict and institutional model for conflict resolution in Banjar Production Forest Management Unit Model in South Kalimantan Province. Five villages taken as samples and respondents consisted of local people and people who have influence on the model. The results showed that lands in Banjar model area by law (de jure) is state property, however, there are villages that are not yet put into enclave. This has caused state property that has closed access in reality became open access (de facto). The condition brought about opportunity set for parties for resource extraction. The land conflict is a structural conflict in which actors involved are not in the same level. Conflict resolution offered is a change from conflict to becomes equal partnership through steps: 1) Trust building, 2) Developing a forestry forum among villages, 3) Independent and competent team mediation, 4) Developing effective communication and 5) Devising regulation consensus.